Identification of a receptor for the morphogen retinoic acid. - Giguere, V.; Ong, E. S.; Segui, P.; Evans, R. M.
Analysis of complementary DNA encoding a novel gene product reveals striking similarity to the steroid and thyroid hormone receptors. Binding and transcription activational studies show it to be a receptor for the vitamin A-related morphogen retinoic acid
Keywords: RETINOIC ACID